Cognitive impairment in depression: recent advances and novel treatments - Perini G (Dove Medical Press, 2019)
Giulia Perini,1,2 Matteo Cotta Ramusino,1,2 Elena Sinforiani,1 Sara Bernini,1 Roberto Petrachi,3 Alfredo Costa1,21Center of Cognitive and Behavioral Disorders, IRCCS Fondazione Mondino, National Institute of Neurology, Pavia, Italy; 2Department of Brain and Behavior, University of Pavia, Pavia, Italy; 3Unit of Mood Disorders, Psychiatry Service, ASST, Acqui Terme, Alessandria, ItalyAbstract: In the past, little or no attention was paid to cognitive disorders associated with depression (a condition sometimes termed pseudodementia). However, recent years have seen a growing interest in these changes, not only because of their high frequency in acute-stage depression, but also because they have been found to persist, as residual symptoms (in addition to affective and psychomotor ones), in many patients who respond well to antidepressant treatment. These cognitive symptoms seem to impact significantly not only on patients’ functioning and quality of life, but also on the risk of recurrence of depression. Therefore, over the past decade, pharmacological research in this field has focused on the development of new agents able to counteract not only depressive symptoms, but also cognitive and functional ones. In this context, novel antidepressants with multimodal activity have emerged. This review considers the different issues, in terms of disease evolution, raised by the presence of cognitive disorders associated with depression and considers, particularly from the neurologist’s perspective, the ways in which the clinical approach to cognitive symptoms, and their interpretation to diagnostic and therapeutic ends, have changed in recent years. Finally, after outlining the pharmacodynamics and pharmacokinetics of the first multimodal antidepressant, vortioxetine, it reports the main results obtained with the drug in depressed patients, also in consideration of the ever-increasing evidence on its different mechanisms of action in animal models.Keywords: depression, major depressive disorder, pseudodementia, antidepressant drugs, vortioxetine, SSRIs